Pochekaev R.Yu. Chinggis Khan’s Great Yasa in the Mongol Empire and Chinggisid States of the 13th–14th centuries: Legal Code or Ideal “Law and Order”? - R.Yu. Pochekaev (Золотоордынское обозрение)
Research objective of the article is clarifying of the nature of the Greta Yasa of Chinggis Khan: was it legal code or set of specific edicts, regulations and principles? Research materials include Arabian and Persian historical sources which already were used by another researchers of the Great Yasa (D. Ayalon, D.O. Morgan), as well as new sources on the history of the Mongol Empire, the Golden Horde, Yuan Empire, Chaghataid state recently introduced into scholarly circulation. Research results of the article consist in getting of arguments that the Great Yasa, in fact, was a set of specific principles and rules established by Chinggis Khan, and their observance provided a harmony in the Mongol Empire and the states of Chinggisids, i.e. the Great Yasa was a kind of “law and order” but not a legal code. Research novelty of the article is represented by analysis of the level of the legal development of the Mongols of the 13th–14th cc. when they didn’t need a special codification to regulate their legal relations, that’s why no one authentic source mentioned the Great Yasa as code of laws and it is characterized in this way only by representatives of the “written legal culture” (European, Caucasus, Arabian, etc.).